2015
DOI: 10.1001/jamainternmed.2015.1849
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of the Homebound Population in the United States

Abstract: Increasing numbers of older, community-dwelling adults have functional impairments that prevent them from leaving their homes. It is uncertain how many people who live in the United States are homebound.OBJECTIVES To develop measures of the frequency of leaving and ability to leave the home and to use these measures to estimate the size of the homebound population in the US population. DESIGN, SETTING, AND PARTICIPANTS Cross-sectional data from the National Health and Aging Trends Study collected in 2011 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
403
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 298 publications
(415 citation statements)
references
References 29 publications
6
403
0
6
Order By: Relevance
“…In addition, these participants had spent most of their life in the city and currently live in a high-income neighbourhood and have a caregiver. These characteristics are in agreement with worldwide studies 9,16,18,19 and emphasise the feminisation of ageing. Among all the independent variables influencing functional dependency, having a caregiver was the most significant factor, which suggests that having someone to provide assistance can increase, on average, 40.2 times (CI95% 4.8; 355.4) the chance of being functionally dependent.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In addition, these participants had spent most of their life in the city and currently live in a high-income neighbourhood and have a caregiver. These characteristics are in agreement with worldwide studies 9,16,18,19 and emphasise the feminisation of ageing. Among all the independent variables influencing functional dependency, having a caregiver was the most significant factor, which suggests that having someone to provide assistance can increase, on average, 40.2 times (CI95% 4.8; 355.4) the chance of being functionally dependent.…”
supporting
confidence: 91%
“…The results of this study showed that 48% of the homebound elderly included in the study were functionally dependent. Conversely, evidence provided by the literature shows a higher prevalence of functional dependency among the homebound elderly 15 and suggests that the higher the functional dependency, the higher the chance of the person being homebound 15,16 . However, the variability among functional independence measurement instruments and procedures makes it difficult to compare prevalence between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated 2 million elderly homebound living in the US have a disproportionate chronic disease burden (14). The homebound often have complex and interrelated medical and social comorbidities that contribute both to substantial functional and cognitive limitations, greater use of health care services, and higher mortality rates compared to the non-homebound elderly population (11, 1419).…”
Section: Introductionmentioning
confidence: 99%
“…Homebound individuals have considerable difficulty leaving the home without assistance (Centers for Medicare and Medicaid Services, 2009). Almost 6% of community-dwelling, elderly Medicare beneficiaries are either mostly or completely homebound, which translates to more than two million Americans and encompasses more people than the current U.S. nursing home population (Ornstein et al, 2015). Homebound patients tend to be frail, elderly, and medically complex (Qiu et al, 2010), often having multiple chronic conditions (Kellogg & Brickner, 2000; American Academy of Home Care Physicians, Public Policy Statement).…”
Section: Introductionmentioning
confidence: 99%